Kamus Digital Tanaman Obat Menggunakan Algoritme Knuth Morris Pratt Berbasis Mobile - Arie Qurania; Triastinurmiatiningsih -; Erika Candra (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2022)
Digital dictionary of medicinal plants a collection of applications a collection of names of medicinal plants. This application was developed to make it easier for users to access the use of medicinal plants based on keywords, names of common diseases such as asthma, diarrhea, fever, headache, diabetes, and so on. The obstacle in using the digital dictionary application of medicinal plants is that it is difficult to find exact information on drug searches, because the vocabulary in producing several other items is not necessarily the same as what is being sought. This study uses the Knuth Morris Pratt (KMP) algorithm search technique on a digital dictionary of medicinal plants by matching keywords as input with strings between text and patterns. This study aims to develop previous research on a digital dictionary of medicinal plants using a mobile-based Rocchio algorithm that searches medicinal plant data by querying proximity in a database that has weaknesses in words that have the same meaning with different words, using another search technique, namely KMP. is expected to get optimal results on search results based on the keyword name of the disease. The test results with 30 keywords on 640 medicinal plant data resulted in a precision value of 92.4, accuracy and recall of 100%.